Análisis previo la implementación de lean manufacturing como herramienta para mejorar la eficiencia en el área de producción de la Empresa JATARIG Cia. Ltda - Bones Briones, Cinthy Carolina (2018)
The present project was carried out in order to propose a lean manufacturing tool in the company JATARIG CIA. LTDA., noting the importance of including these tools and the positive results of the implementation, this in turn will generate a clearer vision regarding the theories of culture organizational To start with the development of a proposal to implement lean manufacturing, the production area was taken, in which several changes are identified that cause some activities to be inefficient, through the presence of failures and errors in the production process, such as cutting process, turning process and assembly process. Consecutively, information was collected to establish the current status of the company and to effectively focus all the solutions regarding the critical areas identified and the causes of these. The analysis of the production process through different matrices allowed to identify the conditions in which the critical events occur. Finally, a lean manufacturing proposal was designed based on the 5'S methodology based on Kaizen, which allowed solving the problems detected.